The Effect of Hygiene Practices and Environmental Sanitation on Stunting Incidence: A Community-Based Public Health Approach - Herlina Lidiyawati (PT. Anagata Sembagi Education, 2026)
Stunting remains a major public health challenge in Indonesia, with long-term consequences for cognitive development, educational attainment, and adult productivity. Beyond inadequate dietary intake, environmental determinants such as poor hygiene practices and inadequate sanitation contribute significantly to impaired linear growth. This study aims to analyze the effect of hygiene practices and environmental sanitation on stunting incidence using a community-based public health approach. A cross-sectional community-based analytical design was applied among children aged 6–59 months. Data were collected through structured caregiver interviews, direct household observations of sanitation facilities, anthropometric measurements based on WHO growth standards, and review of community health records. Multivariate logistic regression analysis was conducted to determine adjusted odds ratios for WASH-related factors. The results indicate that lack of handwashing before feeding, unimproved latrine facilities, unsafe water sources, open defecation practices, and recent diarrheal episodes significantly increase the likelihood of stunting. These findings support the fecal–oral transmission and environmental enteric dysfunction pathways linking sanitation and growth failure. The study concludes that integrated community-based WASH interventions, combined with behavior change strategies and local health system strengthening, are essential to sustainably reduce stunting prevalence